Paving the Way for Circular Supply Chains: Conceptualization of a Circular Supply Chain Maturity Framework - Laura Montag (Frontiers Media S.A., 2021)
The European Green Deal aims to make Europe climate neutral by 2050. According to this ambitious plan, 50% of greenhouse gas emissions are to be saved through a wide implementation of a circular economy. With supply chains responsible for four-fifths of greenhouse gas emissions, their role in the transition from linearity to a circular economy, and thus in the successful implementation of circular systems, is critical and requires the attention of academia, policymakers, and practitioners. Maturity models are suitable for monitoring, assessing, and evaluating the transformation process and determining the status quo of a supply chain. However, as the implementation of circular supply chains is still in its infancy, circular maturity frameworks at the supply chain level are not available yet. Therefore, the purpose of this study is to conceptualize a framework for analyzing the maturity level of circular economy adoption in the supply chain context. From an extensive and systematic literature review of overall 1,372 articles on supply chains, circular economy and maturity the following findings can be drawn: (i) circular economy and circular supply chains are massively growing research streams; (ii) the link between circular economy, supply chains and maturity assessment is so far missing; (iii) three constructs (organization, products, processes) characterize and influence circular supply chain maturity; (iv) a 3-layered maturity grid covering six archetypal elements of the circular economy enables the assessment of a circular supply chain maturity. The developed circular supply chain maturity framework paves the way for circular economy adoption at supply chain level by understanding current level of circular maturity and thus supporting the circular economy implementation process at supply chain level.